Gerontechnology : understanding older adult information and communication technology use - Birkland, Johanna L. H. (Emerald Publishing Limited, 2019)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched Funding, and is freely available to read online. Our aging societies have become increasingly digitalized, leading to concerns that older adults (those age 65 and older) will be disenfranchised by the grey digital divide. However, those familiar with the elder population have long noted a diversity of Information and Communication Technology (ICT) use. While some older adults reject digital technologies, others embrace them with an enthusiasm that mirrors some of the youngest members of our society. Gerontechnology: Understanding Older Adult Information and Communication Technology Use explores, theorizes, and explains this diversity in older adult technology use. Illustrated through interpretive interactionist case studies of 17 older adults and data from their friends, family, and co-workers, the book incorporates perspectives from Gerontology, Communication, and Information Studies in its creation of the ICT User Typology. This typology not only describes the diversity in ICT use, but categorizes older adults' motivations in domesticating technologies into their everyday lives. Focusing not only on technology adoption, it explores the challenges and joys elder users face, and the meanings these technologies come to develop for older adults. Useful for the researcher interested in older adult technology use, domestication studies, and technology adoption; Gerontechnology also provides valuable guidance to those practitioners and service providers who want to understand how older adults use and view technology. Practical implications for designers and advertisers seeking to engage the growing senior market are included.